A slow-release strategy of Lactobacillus plantarum to enhance the degradation of cellulose by Bacillus methylotrophic in the ensiling process of corn stalk - Wan, Yongqing; Liu, Siyuan; Song, Yunhao; Tian, Ruihua; Wang, Ruigang; Duan, Kaihong; Mandlaa, Mandlaa (Frontiers in Microbiology, 2024)
The enhancement of cellulose degradation is important for improving the quality of corn-stalk silage. However, the rapid drop in pH caused by the propagation of lactic acid bacteria (LAB) can influence the degradation of cellulose by cellulose-degrading microorganisms (CDMs) during the mixed fermentation process of ensilage. In this study, a CDM (Bacillus methylotrophic 2–4, BM 2–4) was isolated, and its lyophilization condition was studied. Moreover, a slow-release strategy was developed to delay the release of LAB (Lactobacillus plantarum S-1, LP S-1) by embedding technology to provide time for BM 2–4 to degrade cellulose during the corn-stalk ensilage process. The results showed that BM 2–4 had a higher survival rate (89.53%) under the following conditions: cell collection (5,600 r/min in 4.4°C for 9.5-min centrifugation) and lyophilization using cryoprotectants [skim milk (10.4%), peptone (10.4%), and glucose (5.2%)] at −50°C with a vacuum pressure of <10 Pa. Based on the results of the previous study on embedded LP S-1, simultaneous inoculation of embedded LP S-1 and lyophilized BM2-4 at a 2:1 ratio, with an inoculum size of 6% and moisture content of 85%, significantly degraded CF by 3.8% and increased CP by 3.7% (p < 0.05). This treatment did not significantly influence the final pH of corn-stalk silage (p > 0.05) after 7 days of fermentation.